Does The Entrepreneurship Education Matters in Enhancing Entrepreneurial Skill Among Students in Malaysian Public Universities? - Din, Badariah Haji; Anuar, Abdul Rahim; Usman, Mariana (International Review of Management and Marketing, 2016)
The Malaysian Ministry of Higher Education has implemented the Entrepreneurship Development Initiative to enhance the entrepreneurship education programs in higher learning institutions in order to produce more young entrepreneurs who can create their own jobs. These programs have always been amended to make sure that the structure of the programs fits the challenging and demanding world outside. The purpose of our study is to evaluate the effectiveness of entrepreneurship education program in Malaysian public universities. This study involves of 320 final year students in Bachelor of Entrepreneurship program from six public universities in Malaysia (IPTAs). The primary data are collected to reveal students' perceptions of the effectiveness of the entrepreneurship program and their knowledge about entrepreneurship. The results of this study suggest that an increase in business plan, risk thinking, locus of control and self-achievement lead to increase the level of effectiveness of the entrepreneurship program. The findings of the study are significant as they provide practical insight into the entrepreneurship education practiced by the Malaysian public universities. In addition, the study also contributes to the present literature on the entrepreneurship education program in Malaysia, particularly in presenting the effectiveness of the universities in conducting entrepreneurship education programs. Hence, the findings of this study may give significant contributions to the Malaysian Ministry of Higher Education to improve the education policy in the future, and other higher education institutions are ideally placed to expose students to environments which foster entrepreneurial skills. Keywords: Entrepreneurship Education, Public Universities, Program Effectiveness JEL Classifications: A22, I125, I128